How Education, Financial Literacy, and Planning Affect Financial Management Among MSMEs in Fena Fafan Maluku - Seleky, Roy (Jurnal Informatika Ekonomi Bisnis, 2025)
This study examines the influence of education level, financial literacy, and financial planning on financial management practices among micro, small, and medium enterprises (MSMEs) in Fena Fafan District, South Buru Regency. Using a quantitative approach, data were collected from 31 MSME operators and analyzed using multiple linear regression. The findings reveal that education level and financial literacy do not significantly affect financial management, while financial planning has a strong and positive influence. These results underscore the importance of practical financial behavior over formal education or theoretical knowledge, particularly in geographically isolated and underserved regions. The demographic profile of the respondents, dominated by limited formal education and micro-scale operations, further emphasizes the relevance of applied planning habits. This study contributes to the growing body of research on rural entrepreneurship and highlights the need for context-sensitive financial development programs that prioritize behavior-based interventions over conventional literacy models.